Virtual reality-supported video modeling for enhancing motor skill acquisition in swimming - Sevinc Namli; Kubra Özdemir; Ilhan Sen; Deniz Bedir (BMC Sports Science, Medicine and Rehabilitation)
Abstract To develop successful training methods, effective acquisition of motor skills in swimming is essential. Emerging technologies, such as virtual and augmented reality, offer innovative ways to enhance learning and performance in this area. This study investigates the influence of video modeling (VM) supported by virtual reality (VR) on the swimming performance of novice swimmers compared to conventional training methods. A total of 55 university students participated in the study, divided into two groups: the VR-supported VM group (VRVM) (n = 28) and the traditional swimming group (TSG) (n = 27). While the VRVM group performed VR-supported VM exercises alongside conventional swimming training, the TSG group received only traditional swimming instruction. Performance indicators assessed in the study included distance per stroke (DpS), crawl kick (CK), swimming duration (SwD), heart rate (HR), and rate of perceived exertion (RPE). Both groups received 40-minute weekly swimming sessions over 11 weeks, while the VRVM group also completed 30-minute VR training prior to each session. The results showed that VR-supported VM training significantly improved novice swimmers’ DpS, CK, SwD, and RPE. In conclusion, this study highlights the potential benefits of integrating VR-supported VM techniques into swimming training programs, providing a more effective approach to skill acquisition and performance improvement. Trial Registration ID: NCT06868706, Registered Date: 10/03/2025, retrospectively registered.